PENGARUH PENGGUNAAN FERRITE BEAD DAN VARIASI JENIS BUSI TERHADAP EMISI GAS BUANG CO DAN HC PADA SEPEDA MOTOR YAMAHA SOUL GT TAHUN 2012 - Reza Aji Arafadh; Ranto Ranto; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
The purpose of this research was to determine: (1) The effect of Ferrite Bead on CO and HC exhaust gas emission on the Yamaha Soul GT 2012 motorcycles; (2) The effect of the use variations of the spark plugs type on CO and HC exhaust gas emission on the Yamaha Soul GT 2012 motorcycles; (3) The interaction of the effect of  Ferrite Bead and variations of spark plugs type on CO and HC exhaust gas emission on the Yamaha Soul GT 2012 motorcycles.This research a quantitative type using experimental methods. The data analysis technique descriptive analysis. The research was conducted at the Laboratory of the Surakarta City Transportation Office located at Jl. Menteri Supeno No.7, Manahan, Banjarsari, Surakarta. The tool for measuring CO and HC exhaust gases is the KOREA IYASAKA brand gas analyzer (TYPE AET-4000Q). The subject in this research was the  Yamaha Soul GT 2012 motorcycle. From the results of the research, it can be concluded: (1) The use of Ferrite Bead can reduce levels of CO and HC exhaust gas emission on Yamaha Soul GT 2012 motorcycle. The test results without the use of Ferrite Bead produced CO emission levels of 0.61% and HC of 122.67 ppm. Whereas in testing the use of Ferrite Bead near spark plugs obtained CO emission levels of 0.53% and HC of 101 ppm, and on testing the use of Ferrite Bead near the coil obtained CO emission levels of 0.60% and HC of 122.67 ppm; (2) The use of variations of the spark plugs type can reduce levels of CO and HC exhaust gas emission on Yamaha Soul GT 2012 motorcycle. The results of testing using Standard spark plugs (C7HSA) produce CO emission levels of 0.61% and HC of 122.67 ppm. While testing using Platinum spark plugs (CR7HGP) obtained CO emission levels of 0.59% and HC of 131.33 ppm, and testing using Iridium spark plugs (NGK CR6HIX) obtained CO emission levels of 0.60% and HC of 93.67 ppm; (3) Interaction of the use of Ferrite Bead and variations of the spark plugs type can reduce levels of CO and HC exhaust gas emission on Yamaha Soul GT 2012 motorcycle. Test results show the lowest levels of CO and HC exhaust gas emission, namely the use of Ferrite Bead near the spark plug and the use of Iridium spark plugs ( NGK CR6HIX) with the lowest exhaust gas emission results, namely 0.45% for CO and 80 ppm for HC.